Holocene-aged sedimentary records of environmental changes and early agriculture in the lower Yangtze, China - TAYLOR, DAVID (My University, 2008)
Sedimentary evidence from a total of 21 AMS 14C dates and 192 pollen and charcoal and 181 phytolith samples from three study sites in the archaeologically rich lower Yangtze in China provides an indication of interactions between early agriculturalists and generally highly dynamic environmental conditions. Results suggest that environmental changes influenced agricultural development, and attest the localised environmental impacts of incipient agriculture. Evidence of human activity, in the form of indicators of deforestation and possibly food production, is apparent by ca 7000 BP (early Neolithic or Majiabang). Clearer evidence of human activity dates to ca 4700 BP (late Neolithic or Liangzhu). Extensive, profound and apparently widespread human impacts do not appear until the Eastern Zhou (Iron Age, ca 2800?2200 BP), however, which in the lower Yangtze was a period associated with technological advances in agriculture, increased urbanisation and relatively stable hydro-geomorphological conditions.
PUBLISHED
Keywords: Sedimentary geology; Agriculture -- Yangtze, China; Archaeology -- Yangtze, China; Environmental change -- Yangtze, China